The impact of puberty on the onset, frequency, location, and severity of attacks in hereditary angioedema due to C1-inhibitor deficiency: A survey from the Italian Network for Hereditary and Acquired Angioedema (ITACA) - Cancian, Mauro; Triggianese, Paola; Modica, Stella; Arcoleo, Francesco; Bignardi, Donatella; Brussino, Luisa; Colangelo, Caterina; Di Agosta, Ester; Firinu, Davide; Guarino, Maria Domenica; Giardino, Francesco; Giliberti, Marica; et al. (Frontiers in Pediatrics, 2023)
Hereditary angioedema due to C1-inhibitor deficiency is influenced by hormonal factors, with a more severe course of disease in women. Our study aims to deepen the impact of puberty on onset, frequency, location and severity of attacks. Retrospective data were collected through a semi-structured questionnaire and shared by 10 Italian reference centers of the Italian Network for Hereditary and Acquired Angioedema (ITACA). The proportion of symptomatic patients increased significantly after puberty (98.2% vs 83.9%, p=0.002 in males; 96.3% vs 68,4%, p<0,001 in females); the monthly mean of acute attacks was significantly higher after puberty, and this occurred both in females (median (IQR) = 0,41(2) in the three years before puberty vs 2(2,17) in the three years after, p<0,001) and in males (1(1,92) vs 1,25(1,56) respectively, p<0,001). The increase was greater in females. No significant differences were detected in attack location before and after puberty.